2015
DOI: 10.1111/zsc.12102
|View full text |Cite
|
Sign up to set email alerts
|

Differences in gene flow in a twofold secondary contact zone of pond turtles in southern Italy (Testudines: Emydidae:Emys orbicularis galloitalica,E. o. hellenica,E. trinacris)

Abstract: Using virtually range-wide sampling for three pond turtle taxa (Emys orbicularis galloitalica,\ud E. o. hellenica, E. trinacris), we analyse gene flow across their southern Italian contact zone.\ud Based on population genetic analyses of 15 highly polymorphic microsatellite loci and a\ud mitochondrial marker, we show that the general genetic pattern matches well with the current\ud taxon delimitation. Yet, single individuals with conflicting genetic identity suggest\ud translocation of turtles by humans. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
83
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(87 citation statements)
references
References 71 publications
3
83
1
Order By: Relevance
“…(see Marrone et al 2016a). Such an unexpected decoupling might be due to a recent, human-mediated introduction of the leech to Sicily, which would be also supported by the evidence of the presence of introduced specimens of E. orbicularis from Italy in Lago Urio Quattrocchi (Vamberger et al 2015), or to a natural long-range passive dispersal event of the species, which is reported to be able to be dispersed by non-chelonian vertebrates with aquatic afinity (Vamberger and Trontelj 2007, Bielecki et al 2012, Marrone et al 2016a.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…(see Marrone et al 2016a). Such an unexpected decoupling might be due to a recent, human-mediated introduction of the leech to Sicily, which would be also supported by the evidence of the presence of introduced specimens of E. orbicularis from Italy in Lago Urio Quattrocchi (Vamberger et al 2015), or to a natural long-range passive dispersal event of the species, which is reported to be able to be dispersed by non-chelonian vertebrates with aquatic afinity (Vamberger and Trontelj 2007, Bielecki et al 2012, Marrone et al 2016a.…”
Section: Discussionmentioning
confidence: 78%
“…Although it is morphologically similar to E. orbicularis sensu lato (s.l.) (see Fritz et al 2006), molecular taxonomic studies have unambiguously revealed the presence of significant differences between the two species, which are adelphotaxa (Fritz et al 2005, Pedall et al 2011, Vamberger et al 2015. In spite of the biogeographical and evolutionary importance of this chelonian species and the reduction of its populations caused by habitat destruction, pollution and pathogens, E. trinacris was listed in the IUCN Red List as 'Data Deficient' (van Dijk 2009), thus highlighting the need for further studies aimed at its characterising and monitoring of its health status.…”
mentioning
confidence: 99%
“…; Vamberger et al. ). Pond turtles were captured by hand or with the use of baited traps left overnight in concealed sites.…”
Section: Methodsmentioning
confidence: 96%
“… and Vamberger et al. ;. Each turtle specimen was carefully inspected for the presence of leeches; when these were present, they were collected and fixed in situ in 95% ethanol, and identified according to Minelli ().…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation